Article review: Comparison of octane booster additive for gasoline - Gustiana Awaludin Sobarsah; Nuryoto Nuryoto; Jayanudin Jayanudin (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2021)
Gasoline is a petroleum-derived liquid that is most typically used in internal combustion engines, especially those utilizing spark ignition. Gasoline is a hydrocarbon blend that contains sulfur, nitrogen, oxygen, and other metals. Olefins, aromatics, paraffin, and naphthenes are the four main components of gasoline. An octane number is a unit of measurement for the ignition quality or flammability of gasoline. It is frequently referred to as the research octane number (RON), and it is calculated using a ratio of isooctane to n-heptane. The octane number can be decreased by lengthening the hydrocarbon molecule chain and increasing by branching the carbon chain. Another method is to use an octane number increaser for gasoline as an addition. These are classified as oxygenate, ether, antiknock agent, nanoparticles, and aromatic compounds. Numerous studies have been conducted to establish the influence of additives in gasoline on engine performance metrics such as braking power, thermal brake efficiency, volumetric efficiency, fuel consumption efficiency, and their impact on the environment. This review article aims to assess and compare the effects of various gasoline additives on the performance and emission characteristics of ignition engines. Bensin adalah cairan yang berasal dari minyak bumi yang paling banyak digunakan sebagai bahan bakar di mesin pembakaran internal, khususnya mesin menggunakan percikan pengapian. Bensin adalah campuran hidrokarbon dengan beberapa kontaminan, termasuk belerang, nitrogen, oksigen, dan logam tertentu. Empat kelompok penyusun utama bensin adalah olefin, aromatik, parafin, dan naften. Angka oktan adalah ukuran kualitas pengapian atau mudah terbakarnya bensin, biasa disebut Research Octane Number (RON) yang dapat diukur menggunakan perbandingan antara campuran isooktana dengan n-heptana. Angka oktan dapat berkurang dengan bertambahnya panjang rantai dalam molekul hidrokarbon sedangkan angka oktan dapat meningkat dengan membuat percabangan rantai karbonnya. Cara lain untuk meningkatkan angka oktan adalah ditambakan peningkat angka oktan bensin sebagai aditif, yang terbagi pada kategori oxygenat, eter, agen antiknock, nano partikel dan senyawa aromatik. Banyak penelitian tentang penggunaan aditif dalam bensin untuk menentukan pengaruhnya terhadap ukuran kinerja mesin seperti daya pengereman, efisiensi rem termal, efisiensi volumetrik, efisiensi konsumsi bahan bakar, dan efeknya terhadap lingkungan. Tujuan dari artikel review ini adalah untuk mengevaluasi serta membandingkan berbagai aditif pada bensin dan pengaruhnya terhadap kinerja dan karakteristik emisi mesin pengapian.